THE INFLUENCE OF SOCIAL MEDIA MARKETING, ONLINE CUSTOMER REVIEWS AND INFLUENCER ENDORSEMENTS ON PURCHASE DECISIONS MODERATED BY CONSUMER TRUST ON THE TIKTOKSHOP MARKETPLACE IN JAKARTA - Sarah Ratu Alizia; Imam Suryono; Sri Sukartono Nathadiharja (RADJA PUBLIKA, 2026)
This study examines the influence of Social Media Marketing, Online Customer Reviews, and Influencer Endorsements on Purchase Decisions, with Consumer Trust as a moderating variable among TikTok Shop users in Jakarta. A quantitative approach was applied using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Data were collected from 165 respondents selected through purposive sampling, consisting of consumers who had purchased products through TikTok Shop and lived in Jakarta. The results indicate that Social Media Marketing, Influencer Endorsements, and Consumer Trust positively and significantly influence purchase decisions. Meanwhile, Online Customer Reviews have a significant but negative effect on purchase decisions. Consumer Trust significantly moderates the relationship between Social Media Marketing and purchase decisions with a weakening effect, while it strengthens the influence of Online Customer Reviews on purchase decisions. However, Consumer Trust does not significantly moderate the relationship between Influencer Endorsements and purchase decisions. These findings highlight the importance of effective digital marketing, credible online reviews, and strong consumer trust in enhancing purchase decisions on TikTok Shop.